Geochemical characterization of zircon in the Fyfe Hills of the Napier Complex, East Antarctica - Takehara, Mami; Horie, Kenji; Hokada, Tomokazu (Zenodo, 2020)
Table S1: The U-Pb and O isotopic data of YH05021606A zircons, Table S2: The REE data of YH05021606A zircons.